Genetic variability, character association and path analysis for yield and its related traits in rice (Oryza sativa L.) genotypes - Singh, S. K.; Singh, Pooja; Khaire, Amrutlal R.; Korada, Mounika; Singh, D. K.; Majhi, Prasanta Kumar; Jayasudha, S. (Sciencedomain International, 2021)
Assessment of variability and trait associations in a crop helps to enhance selection efficiency. With this objective, a study was conducted to estimate the genetic variability, character association and path coefficient analysis for grain yield and its component traits in 80 rice genotypes during Kharif-2020. Eighty genotypes including eight checks were evaluated in alpha lattice design with three replications. For all of the traits studied, the results revealed significant variance in all genotypes.PCV was found to be slightly more than the corresponding GCV for all the characters, indicating the role of environment in the expression of these traits. However, high GCV and high PCV were observed for number of effective tillers, grain yield per plot, number of filled grains per panicle, number of unfilled grains per panicle, biomass yield, harvest index, grain yield per plant and grain yield per hectare. Furthermore, all of the variables investigated had strong heritability and high genetic progress as a percentage of mean, with the exception of days to 50% blooming, days to maturity, and kernel breadth. Days to first flowering, days to 50% flowering, days to maturity, spikelet fertility percentage, number of filled grains per panicle, harvest index and kernel length showed a significant and positive association with grain yield per plot. Highest direct contribution to grain yield per plot was manifested by kernel length, harvest index and spikelet fertility percent. Days to first flowering, days to maturity, number of effective tillers, number of unfilled grains per panicle, test weight, biomass yield were also found to exert a positive effect on yield, thus can be considered as desirable traits for selection in high yielding genotypes.